A Phase 1 Pharmacokinetic Drug Interaction Study of Belumosudil Coadministered With CYP3A4 Inhibitors and Inducers and Proton Pump Inhibitors. Issue 7 (1st March 2022) - Schueller, Olivier; Willson, Ashley; Singh, Nand; Lohmer, Lauren; Alabanza, Anginelle; Patel, Jeegar
Abstract: Belumosudil is a selective Rho‐associated protein kinase 2 inhibitor. Inhibition of Rho‐associated protein kinase 2 has emerged as a promising treatment for chronic graft‐versus‐host disease by restoring immune homeostasis and reducing fibrosis. In vitro assessments have suggested that metabolism of belumosudil is primarily dependent on cytochrome P450 (CYP) 3A4 activity and that the solubility of belumosudil is pH dependent. As such, this 2‐part clinical drug‐drug interaction study was conducted to assess the effect of itraconazole (a strong CYP3A4 inhibitor), rifampicin (a strong CYP3A4 inducer), rabeprazole, and omeprazole (both proton pump inhibitors) on the pharmacokinetics of belumosudil. No clinically relevant change in belumosudil exposure was observed following a 200‐mg single oral dose of belumosudil with itraconazole; however, exposure of main metabolite, KD025m2, was decreased. Consistent with the proposed metabolic pathway of belumosudil, the strong CYP3A4 inducer rifampicin significantly decreased exposure of belumosudil and KD025m2 and increased KD025m1 exposure. When a 200‐mg single oral dose of belumosudil was coadministered with both rabeprazole and omeprazole, parent and metabolite exposures were largely reduced, suggesting that belumosudil dosage should be increased when given with PPIs. Administration of belumosudil with and without perpetrator drugs was safe, and no notable adverse events were reported.